(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores the factors affecting the economic efficiency of business entities operating within Uzbekistan’s Free Economic Zones (FEZs), focusing on the zones of Navoiy, Jizzakh, and Angren. Drawing upon statistical data from 2018 to 2023, this study uses a quantitative research design involving ratio analysis and regression modeling to assess the extent to which investment volume, infrastructure, export potential, and employment levels impact efficiency. The research finds that a combination of well-targeted investments and infrastructural improvements significantly contribute to enhanced business performance. Policy recommendations are made based on empirical evidence.